2012
DOI: 10.2298/gensr1201081b
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of wild fruit species of Serbia

Abstract: Several field collecting trips in the 2009-2011 period confirmed that forest fruit species are an inexhaustible genofond of extremely important varieties that yield fruit of excellent quality and high nutritive value, with wide range of applications, including nutritional, medicinal and food production. The aim of this work was to develop long term interactive and integrated strategy for selection of wild fruit species through different breeding methods, as well as popularization of selected products and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 8 publications
2
30
1
Order By: Relevance
“…Fruit mass results of our selections were found between limits of previous studies (Bijelić et al 2008b;Bijelić et al 2010;Ercisli et al 2011;Hassanpour et al 2012). However, Yilmaz et al (2009) and Bošnjaković et al (2012) reported exceptional high fruit mass for some selections such as 9.17 g for 77-05 genotype in Turkey and 14.55 g for VR-10 genotype in Serbia, respectively. the researcher (0.75 and 3.10 %).…”
Section: Physical Characteristicssupporting
confidence: 71%
See 2 more Smart Citations
“…Fruit mass results of our selections were found between limits of previous studies (Bijelić et al 2008b;Bijelić et al 2010;Ercisli et al 2011;Hassanpour et al 2012). However, Yilmaz et al (2009) and Bošnjaković et al (2012) reported exceptional high fruit mass for some selections such as 9.17 g for 77-05 genotype in Turkey and 14.55 g for VR-10 genotype in Serbia, respectively. the researcher (0.75 and 3.10 %).…”
Section: Physical Characteristicssupporting
confidence: 71%
“…Montenegro is located in the south-western part of the Balkans, bordering the Adriatic Sea and it has continental Balkan climate inside and Mediterranean climate in Adriatic side (Mratinić and Kojić 1998;Ognjanov et al 2009;Bošnjaković et al 2012). The country ranks among the territories with the highest level of biological diversity in Europe mostly due to different environmental conditions, varying from cold and wet continental to dry and hot Mediterranean climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Balkan Peninsula is one of the most valuable secondary centers of genetic diversity and provides an inexhaustible gene pool for breeding work in Prunus sp. (Ognjanov et al, 2009;Bošnjaković et al, 2012). 'Oblačinska' sour cherry (Prunus cerasus L.) has been used for decades as a dwarfing rootstock for sweet and sour cherry in Serbia as a population cultivar, but it has never been of national interest to conserve and utilize germplasm for rootstock breeding .…”
Section: Introductionmentioning
confidence: 99%
“…The Balkan Peninsula has also been cited as an important center of diversity for C. avellana (Bošnjaković et al, 2012). Hazelnuts are an ancient crop in the Republic of Georgia, where commercial and backyard garden production is still common and the forests also hold wild trees, making it a promising location to be explored for hazelnut genetic resources.…”
Section: Introductionmentioning
confidence: 99%